Using of Comic-Based Supplementary Material in Enhancing Studentsâ€™ Engagement and Food Preservation Competencies - Joyce Ann De Guzman; Edilberto Z. Andal, EdD (Journal of General Education and Humanities, 2023)
The study assessed the relationship between studentsâ€™ engagement and Grade 6 Food Processing students' competencies concerning their perception of the comic-based supplementary material. Technology and Livelihood Education (TLE) has minimal studies about such concepts, so further research is needed. Â A description-correlation research method involving 30 Grade 6 students and a researcher-made questionnaire was utilized in data gathering. The findings revealed that the comic material was positively recognized by the students with an overall mean of 4.76 with a verbal interpretation of â€œstrongly agree,â€ while the overall mean of perceived student engagement after using the instructional material was 4.72, with the category "highly engaged" reflects that the material helped the learners to be engaged in learning the subject. Furthermore, the relationship between the perception of the use of comic material and engagement was significant, with a high positive correlation r=0.82. It implies that as students utilized the comic material, their engagement increased. Similarly, it was found that student's perception of the comic material was partially significant to their competencies with moderate association r=.39. This is because of the non-significant result of the correlation between the comic and other variables in competencies such as content, presentation, and accuracy. Nonetheless, the material still contributed to learnersâ€™ acquisition of acceptable grades in Food Preservation 6